Preparation of Future Physics Teachers for Research Activities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article describes the basic concepts of methodology and methodological knowledge, as well as research activities of future physics teachers. The preparation of future physics teachers for research activities is a crucial aspect of modern pedagogical education. This article explores effective methods and strategies for developing research competencies in physics teacher training programs. It highlights the importance of integrating scientific inquiry into the curriculum, fostering critical thinking, and enhancing experimental skills. The study also examines the role of research projects, collaboration with scientific institutions, and the use of modern technologies in shaping future educators capable of conducting independent research and implementing innovative teaching approaches.